Synthesis and characterization of Na-P1 (GIS) zeolite using a kaolinitic rock - Daniela Novembre (Nature Portfolio, 2021)
Abstract This work focuses on the hydrothermal synthesis of Na-P1 zeolite by using a kaolinite rock coming from Romana (Sassari, Italy). The kaolin is calcined at a temperature of 650 °C and then mixed with calculated quantities of NaOH. The synthesis runs are carried out at ambient pressure and at variable temperatures of 65 and 100 °C. For the first time compared to the past, the Na-P1 zeolite is synthesized without the use of additives and through a protocol that reduces both temperatures and synthesis times. The synthesis products are analysed by X-ray diffraction, high temperature X-ray diffraction, infrared spectroscopy, scanning electron microscopy and inductively coupled plasma optical emission spectrometry. The cell parameters are calculated using the Rietveld method. Density and specific surface area are also calculated. The absence of amorphous phases and impurities in synthetic powders is verified through quantitative phase analysis using the combined Rietveld and reference intensity ratio methods. The results make the experimental protocol very promising for an industrial transfer.